Basic Concepts and Importance of Educational Materials Development for Teachers and Students: General Theoretical Ideas - Andri Irawan (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
The writing of this article aims to examine several aspects that allow it to provide a fundamental conceptual understanding of educational teaching materials, including the basic concepts of materials, types and development of teaching materials. The writing of this article is a literature study. As for data collection, the author takes references from various journal articles and so on from sources that are in accordance with the topics discussed in this article, so that all data taken can be processed and analyzed properly. The conclusions in this article include that, (1) Teaching materials are a set of subject matter that refers to the curriculum system used with the aim of achieving predetermined competency standards and basic competencies; (2) Teaching materials have several urgent characteristics including self-instructional, integrated (self-contained), stand-alone, adaptive, and user-friendly; (3) Educational teaching materials have various types, including printed and non-printed teaching materials. Examples of printed teaching materials include books, modules, brochures, and LKPD. The non-print teaching materials include audio visual, such as video/film, Video Compact Disc (VCD), then audio forms, such as radio, cassettes, audio Compact Disc (CD), vinyl records (PH), visual forms such as photos, pictures, models / packages. And the last is in the form of multi-media, such as interactive CDs, Computer Based and the Internet; (4) Development of teaching materials means an effort to improve the aspects of the usefulness of teaching materials in education so that they can be developed as widely as possible, so that it is possible to have an optimal positive effect on educational goals in accordance with what is expected.